The impact of opportunistic behavior on reducing the quality of financial reports - an analytical study in Al-Rafidain and Al-Rasheed banks in Najaf: Dampak perilaku oportunistik terhadap penurunan kualitas laporan keuangan - sebuah studi analitis di bank Al-Rafidain dan Al-Rasheed di Najaf - Huda Ameen Oleiwi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Financial reporting quality is essential for transparency and accountability in the banking sector. Specific Background: Opportunistic behavior by managers, such as self-interest seeking and lack of commitment, can distort financial information and reduce the credibility of financial reports. Knowledge Gap: Empirical evidence examining the relationship between opportunistic behavior and financial reporting quality in emerging banking contexts such as Najaf remains limited. Aims: This study examines the relationship between opportunistic behavior and financial reporting quality among employees of Al-Rafidain Bank and Al-Rasheed Bank in Najaf. Results: The findings show a low level of opportunistic behavior (mean 1.614) and a relatively high level of financial reporting quality (mean 3.978), with accuracy recording the highest value. Statistical analysis confirms a significant negative relationship between opportunistic behavior and financial reporting quality. Novelty: The study links behavioral dimensions of opportunism with the dimensions of accuracy, reliability, and readability of financial reporting within the Iraqi banking sector. Implications: The results emphasize the importance of ethics training, governance mechanisms, and adherence to reporting standards to maintain reliable financial reporting practices. Highlights• Strong negative statistical relationship identified between opportunistic conduct and reporting credibility• Highest evaluation recorded for statement precision dimension• Respondents reported minimal tendency toward self-serving managerial actions KeywordsOpportunistic Behavior; Financial Reporting Quality; Banking Sector; Agency Theory; Corporate Governance